2021
DOI: 10.3906/kim-2008-34
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated FeIII/FeII redox cycle of Fenton reaction system using Pd/NH2-MIL-101(Cr) and hydrogen

Abstract: In this paper, a novel improvement in the catalytic Fenton reaction system named MHACF-NH 2 -MIL-101(Cr) was constructed based on H 2 and Pd/NH 2 -MIL-101(Cr). The improved system would result in an accelerated reduction in Fe III , and provide a continuous and fast degradation efficiency of the 10 mg L -1 4-chlorophenol which was the model contaminant by using only trace level Fe II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…They could be rapidly mineralized by ˙OH. 31–33,40,41,43,44 As can be seen in Fig. 7(a), during a 3 h reaction process, the removal efficiencies of SMT and 4-CP were 94.23% and 100% in the MHACF-UiO-66(Zr) system, respectively, while they were 20.98% and 99.33% in the Fenton system.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…They could be rapidly mineralized by ˙OH. 31–33,40,41,43,44 As can be seen in Fig. 7(a), during a 3 h reaction process, the removal efficiencies of SMT and 4-CP were 94.23% and 100% in the MHACF-UiO-66(Zr) system, respectively, while they were 20.98% and 99.33% in the Fenton system.…”
Section: Resultsmentioning
confidence: 90%
“…The degradation efficiency of refractory organics in both the MHACF-MIL-101(Cr) system and MHACF-NH 2 -MIL-101(Cr) system significantly decreased with the continuous structure destruction of MIL-101(Cr) and NH 2 -MIL-101(Cr) in acidic conditions. 31–33…”
Section: Introductionmentioning
confidence: 99%
“…The nano-Pd 0 particle would gradually fall off during the reaction. Compared with the MIL-101(Cr) and NH 2 -MIL-101(Cr) used in our previous works [ 12 ], the MIL-100(Fe) had better durability. However, it was slightly less durable than that of UiO-66(Zr) and MOF-808(Zr) [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 95%
“…However, it was slightly less durable than that of UiO-66(Zr) and MOF-808(Zr) [ 13 , 14 ]. According to the soft and hard acid theory, this is because the high-priced metals have stronger acid resistance [ 12 ]. Firstly, we found the sole activity-MHACF-MIL-100(Fe) by differential experiments, and then we proved the presence of the main reactive oxygen ion -OH in the system by the probe capture method; then we explored the Fe III /Fe II cycle in the MHACF-MIL-100(Fe) system, and found that the Fe III /Fe II cycle in the MHACF-MIL-100(Fe) system is highly efficient, which makes this system have the ability of sustainable oxidation downgrade SMT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation